Incisional hernia of giant abdominal wall: a case report - Carvalho, Beatriz Monteiro de (2022)
Incisional hernia results from inadequate healing in the area of an operative incision and its diagnosis is clinical or imaging. Complex incisional hernias are difficult to treat and have complications, especially compartment syndrome. Thus, technical care in closing incisions in primary surgeries reduces the risk of developing an incisional hernia. Therefore, the study aimed to present a case report of a patient who performed the present correction of a giant incisional hernia with a double-sided mesh.